Sleep pattern and associated risk factors among a medical college staff - Shridevi, Kotina; Kokiwar, Prashant R.; K, Sushma; Chauhan, Pooja; Gaiki, Varun (International Journal Of Community Medicine And Public Health, 2017)
Background: Sleep is a resting state during which the body is inactive and mind unconscious. Poor sleep quality means sleep that is interrupted by wakening. Bad quality of sleep is associated with psychiatric disorders, car and automobile accidents, early aging, depression, kidney failure, glucose intolerance, hypercortisolemia, hypertension, Type 2 diabetes, obesity, decreased efficiency at work, increased chances of death etc. Objectives of the study was to know sleep quality pattern in medical community of a medical college and to determine poor sleep quality and associated risk factors. Methods: The present study design was a community based cross sectional study. Sample size calculated using the formula n=p ((1-p)/e2. Data collection was done for 5 days. Data was collected from the faculty and other working staff using PSQI questionnaire. Participants scoring more than five points were classified as bad sleepers. The filled questionnaires was entered on Microsoft Excel. The results were tabulated and presented in percentages, t test and chi square. Results: 41.2% (63) of the participants were having poor sleep.8 (5.23%) were having worst range of sleep efficiency. 18(11.76%) did not use any medication for sleeping. 45(29.42%) participants had trouble staying awake while driving, eating meals or engaging in social activities. Participants were having the habit of Tea, Alcohol, smoking and exercise and there was no significant difference between both the groups. Associated risk factors found in both the groups were Hypertension, Diabetes, Fatigue, Lack of concentration, loss of memory and back pain. Significant difference was seen only in Lack of concentration. Conclusions: Participants were having the habit of Tea, Alcohol, smoking and exercise and there was no significant difference between both the groups. Associated risk factors found in both the groups were Hypertension, Diabetes, Fatigue, Lack of concentration, loss of memory and back pain.